LEAN SERVICE IMPLEMENTATION PROPOSAL TO INCREASE MAINTENANCE SERVICE QUALITY AT PRIMERO INNOVA S.A.C., LIMA (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
This research presents a Lean Service-based proposal to improve the quality of medical equipment maintenance services at Primero Innova S.A.C. in Lima during 2025, aiming to optimize response capacity, reliability, and safety. Using a non-experimental, descriptive, and propositional design, 194 service orders from January to December 2024 were analyzed, of which only 134 were addressed. Descriptive statistical techniques were applied to records of response times, service orders, and complaints. The results revealed an average waiting time of 7 days, a 69.07 % service order completion rate, an average diagnostic time of 18 minutes, a 36.57% incidence repetition rate, and a 74.63 % complaint index, highlighting operational inefficiencies. The Lean Service proposal, based on tools such as Value Stream Mapping (VSM), Kanban, and standardization, projects 100 % service order fulfillment, reduced waiting, diagnostic times and decreased complaints. The proposal requires an initial investment of S/28,560.00, with a projected ROI of 56.56% and a recovery period of 2 months. It is estimated to increase annual revenue to S/274,365.22 and reduce inefficiency costs by S/84,855.22. In conclusion, the Lean Service proposal is technically and economically viable, optimizing processes, enhancing customer satisfaction, and strengthening the company’s competitiveness, offering an adaptable model for Peru’s healthcare sector.
Keywords: Lean Service; service quality; responsiveness; reliability; safety